How the Corporate Social Responsibility (CSR) Strategies Affect Corporate Financial and Non-financial Performance in FMCG Apparel Industry, A Chinese Context - NI, MIDI (2020)
There have been many quantitative studies that focus on the impact of corporate social responsibility (CSR) on financial performance in decades. Some scholars study the relationship between CSR and some non-financial performance indicators, such as consumers and employees-relating aspects performance. The fast-moving consumer goods (FMCG) apparel industry has gained momentum in recent years and has shown development in China, but the emphasis on social responsibility within this industry is uneven in the context of China. Little studies have been conducted with this background. To fulfill a research gap in this area, this dissertation selects a representative company in this industry, UNIQLO as a business practice and applies qualitative content analysis to conduct research. The research aim is to discover how CSR affects different forms of performance in this industry, and how the links are realized with CSR strategies. The assumption which is based on the results of previous studies, is that the strategic layout and implementation of CSR is beneficial to the growth of both financial and non-financial performance. This dissertation combines the CSR pyramid model with a representative company’s CSR strategies to explore the links. The findings confirm the value of social responsibility in the FMCG apparel industry. If properly planned, the strategic management on CSR will benefit for the financial and non-financial performance in a long term.